Effects of Continuous Use of Nitrogen Alone and In Combination with Phosphorus and Potassium Fertilizers on Plant Available Major and Secondary Nutrients in Soil under Wheat-Rice Intensive Crop Rotation: Impacts of Continuous Fertilizer Use on Soil Nutrient Availability and Crop Productivity (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Available phosphorus of the soil, decreased with nitrogen application as compared to control. Addition of phosphorus over nitrogen significantly increased phosphorus content. It was increased by 68-80 per cent with combine application of NPK and decreased 13 per cent under the plots receiving N-alone as compared to control. The potassium fertilization over NP further improved phosphorus content. The nitrogen fertilizer alone and phosphorus lowered potassium availability by 3 and 5 per cent, respectively, over no fertilizer. The availability of Potassium declined by about 2 per cent after Wheat and Rice harvest in each year. Sulphur availability improved by 27 and 22 per cent under N,P and NPK treatments, respectively, whereas its availability decreased 6 percent under nitrogen alone over control.The continuous application of fertilizers N, P and K could help to improve such nutrients deficiencies due to imbalanced application of fertilizers under intensive farming systems.With high yielding varieties in an intensive cropping system. The depletion of sulphur and micronutrients not being added through fertilizers become more rapid. As the demand for higher yield goes up and the plant requirements for N,P and K are more efficiently met through fertilizers, sulphur and micronutrients in the soil are likely to become limited. According to Williams and Steinbergs (1959) the soil should contain at least 10 ppm of sulphate-sulphur for normal plant growth. Anand Svarup and Ghose (1980) found a rapid decrease in water extractable sulphate in soil where diammonium phosphate was applied continuously as phosphorus source in a long term field experiment.In the interest of sustained crop productivity at high levels of fertilization, it is necessary to look farward into the effect of continuous manuring fertilization and cropping practices both on the yield as well as on the fertility status of the soil. By considering these views, Laws and Gilbert started the world's oldest classical manurial experiment in 1843 at Broadbalk field in Rothamsted (England). India also started a few long term manurial experiments on Rothamsted model at Kanpur in 1885, Pusa (Bihar) in 1908 and Coimbatore (Madras now TamilNadu) in 1909. However, these experiments were initiated under dryland condition and did not meet the requirements of the modern intensive farming production system.